P uptake and growth of maize (Zea mays L.) due to the combination of organic matter and SP-36 fertilizer on Ultisol - Wida Akasah; Fauzi Jamal; Mohd Madjid Damanik (Universitas Sumatera Utara, 2018)
The objective of this research is to know the uptake of P and growth of maize (Zea mays L.) due to the combination of organic material and SP-36 on Ultisol. This study used randomized block designed which consist of 2 factors and 3 replications. The first factor is organic material: A (0 ton/ha), B (30 ton/ha husk-pulp compost of Durio zibethinus), C (22,5 ton/ha husk-pulp compost of Durio zibethinus + 7,5 ton/ha chicken manure), D (15 ton/ha of husk-pulp compost of Durio zibethinus + 15 ton/ha chicken manure), E (7,5ton/ha husk-pulp compost of Durio zibethinus +22,5 ton/ha chicken manure), F (30 ton/ha chicken manure) and the second factor is SP-36 : P0 (0 kg P2O5/ha), P1 (100 kg P2O5/ha), P2 (200 kg P2O5/ha), P3 (300 kg P2O5/ha). The results showed that the combination of organic materials significantly influenced soil pH, C-Organic, P-Potential soil, P uptake, stem diameter, dry weight and dry root plant. Aplication SP-36 fertilizer significantly increased P-Potential soil, P plant uptake, stem diameter, dry weight and dry root plant. The interaction of combination of organic matter and SP-36 fertilizer significantly increased P plant uptake. Best dose on this research is 7,5 ton/ha of husk-pulp compost of Durio zibethinus and 22,5 ton/ha chicken manure and 200kg P2O5/ha of SP-36 fertilizer.